Utilizing Hirshfeld surface calculations, non-covalent interaction (NCI) plots and the calculation of interaction energies in the analysis of molecular packing - Tan, Sang Loon *; Jotani, Mukesh M.; Tiekink, Edward R. T. * (International Union of Crystallography, 2019)
The analysis of atom-to-atom and/or residue-to-residue contacts remains a favoured mode of analysing the molecular packing in crystals. In this contribution, additional tools are highlighted as methods for analysis in order to complement the ‘crystallographer’s tool’, PLATON [Spek (2009). Acta Cryst. D65, 148–155]. Thus, a brief outline of the procedures and what can be learned by using Crystal Explorer [Spackman & Jayatilaka (2009). CrystEngComm 11, 19–23] is presented. Attention is then directed towards evaluating the nature, i.e. attractive/weakly attractive/repulsive, of specific contacts employing NCIPLOT [Johnson et al. (2010). J. Am. Chem. Soc. 132, 6498–6506]. This is complemented by a discussion of the calculation of energy frameworks utilizing the latest version of Crystal Explorer. All the mentioned programs are free of charge and straightforward to use. More importantly, they complement each other to give a more complete picture of how molecules assemble in molecular crystals.